ENGLISH COURSE SEBAGAI MEDIA PENINGKATAN SUMBER DAYA MANUSIA WARGA BR. BABAKAN CANGGU - Juliarta, I Made (LPPM IST AKPRIND Yogyakarta, 2021)
This community service activity aimed to improve the quality of human resourceswhich was carried out by means of English language training. This English training waspackaged in the form of an English Course / basic English training. This program wasinitiated thanks to the collaboration between the educators themselves and the Br BabakanCanggu community, and the Canggu language consultant to prepare human resources whoare ready to compete in the world of work in the current 4.0 era. This English course /training was held for 4 months at Br. Babakan Canggu North Kuta, Badung. The persuasivemethod is a method used in the learning process. The training provided to the participantsincluded basic level English language training and Indonesian language training for foreignspeakers. All English language training participants were very enthusiastic in participatingin the English training process which was held in collaboration with the language andcommunity consultancy agency Br Babakan Canggu, North Kuta, Badung. The process ofEnglish training provided to Babakan, Canggu residents is based on sincere sincerity.